Politik Ekonomi Pada Industri Hiburan SPA di Kota Denpasar (Studi Pada X SPA Denpasar) - Agnes Arijesni, Ni Ketut Lola; Bandiyah, Bandiyah; Noak, Piers Andreas (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2021)
This study aims to analyze the Political Economy Interaction in the Entertainment Industry, a case study: X SPA in Denpasar City. The research objectives include: (1). know how SPA owners interact with the Denpasar City government, therapists and indigenous peoples and provide an overview of indigenous peoples' assumptions about the SPA industry. The theory used is the State and Legality theory studied by Edwardd Aspinall. Data collection was carried out by means of observation, interviews and documentation. The findings of this study indicate that the prostitution business occurs due to large market competition, so that the owners of the SPA industry change their business into a prostitution business for personal gain, so that many people or big actors who use their power do not comply. with outstanding government regulations. Often the power of actors is misused for personal gain and oppresses the common people or society without power in general. Keywords: Ilegality, SPA, SPA Prostitution.